Fast reactor power stations proceedings of the international conference organized by the British Nuclear Energy Society held on 11-14 March, 1974 at the Institution of Civil Engineers, London. (British Nuclear Energy Society, 1974)
Proceedings of an international conference held on 11-14 March 1974.